A solution to the conflicts of multiple planning boundaries: Landscape functional zoning in a resource-based city in China. (July 2018) - Liu, Yanxu; Fu, Bojie; Zhao, Wenwu; Wang, Shuai; Deng, Yu
Abstract: How can planners integrate multiple planning processes with conflicting spatial boundaries from various administrative departments? This question presents one of the key obstacles in China's current spatial planning practices and has aroused controversy among planners from diverse disciplinary backgrounds. Focusing on the differences in spatial scale between economic and social development planning, land use planning and urban master planning, this study explores an integration of multiple planning approaches at different spatial scales based on a landscape functional zone (LFZ) analysis for Hebi City, a resource-based city in China. The landscape has been segregated into cultivated landscapes, ecological landscapes and urban landscapes, with rigid and conditional restriction levels for either dominant landscapes or coherent landscapes. In the result, the landscape was zoned into 11 classifications based on the 22 restriction and suitability indicators. Rigidly restricted cultivated landscapes accounted for 45.37% of the total area, and conditionally restricted ecological landscapes ranked second with 12.52% of the total area. With regard to the context-dependent planning debate of land sharing/land sparing, the LFZ is able to support land-use policy making at the landscape scale. To conclude, the LFZ could be an innovative solution to the planning conflicts because it clarified the spatial difference of land use in the zones and limited the conflicts of multiple planning boundaries to a few local multifunctional landscape patches. Highlights: The conflicted spatial planning boundaries confused the planners. Landscape functional zone (LFZ) is proposed for integrate multiple plans. Rigid and conditional restriction levels are introduced. Five suitability levels are segregated. LFZ is a supplement for the Major Function Oriented Zone at the county level.